2020
DOI: 10.1186/s12939-020-1139-3
|View full text |Cite
|
Sign up to set email alerts
|

The disequilibrium in the distribution of the primary health workforce among eight economic regions and between rural and urban areas in China

Abstract: Background: Equity is one of the major goals of China's new medical reforms launched in 2009. This study aimed to analyze the disequilibrium in primary health care (PHC) workforce among various economic zones in China and to compare the fairness between urban and rural areas since the implementation of the new medical reforms.Method: According to China's 11th Five-Year Plan, China is divided into eight economic regions. The data of this study were obtained from China Statistical Yearbook 2009-2016. The Atkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 13 publications
4
39
0
1
Order By: Relevance
“…The distribution of health care resources in Jiangsu Province is generally fair: the fairness distribution according to the population is higher than that according to the geographical area, and the distribution of primary health resources is better than that of financial resources. This finding is consistent with the results of other studies on the equity of health resource allocation in China [24,25]. There are two main reasons for this result: on the one hand, the policies issued by the government aim mainly to meet the medical needs of the population, not the needs of the regional layout [26]; on the other hand, there is a gap in the economic development of Jiangsu Province, which has a certain impact on the supply of medical resources [16].…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of health care resources in Jiangsu Province is generally fair: the fairness distribution according to the population is higher than that according to the geographical area, and the distribution of primary health resources is better than that of financial resources. This finding is consistent with the results of other studies on the equity of health resource allocation in China [24,25]. There are two main reasons for this result: on the one hand, the policies issued by the government aim mainly to meet the medical needs of the population, not the needs of the regional layout [26]; on the other hand, there is a gap in the economic development of Jiangsu Province, which has a certain impact on the supply of medical resources [16].…”
Section: Discussionsupporting
confidence: 93%
“…Li and Wang carried out regression analysis on different factors that could influence PMHE, and found that fiscal decentralization, household registration system, medical and health system reform, urbanization level, economic development level, population density, and education level have significant influence on input-output efficiency in China [18]. Cheng and Liao, Wang et al believed that fiscal decentralization, population density, together with education level have significant impacts on the efficiency of public health care in China [19,20]. The difference is that the Chen and Liao believed that both of those two had significant positive impacts, while Wang and Tao believed they had negative effects [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheng and Liao, Wang et al believed that fiscal decentralization, population density, together with education level have significant impacts on the efficiency of public health care in China [19,20]. The difference is that the Chen and Liao believed that both of those two had significant positive impacts, while Wang and Tao believed they had negative effects [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical results show that the regional distribution of medical institutions, medical staff, and beds in China is extremely uneven, with the Gini coefficient exceeding 0.7 [7]. In addition, in terms of primary health care and urban and rural medical services, there are significant differences in different regions [8]. Some theorists have suggested that the "economic status of cities accounted for most of the existing inequality" [9].…”
Section: Introductionmentioning
confidence: 99%